2019
DOI: 10.1111/jir.12630
|View full text |Cite
|
Sign up to set email alerts
|

The impact of behavioural skills training on the knowledge, skills and well‐being of front line staff in the intellectual disability sector: a clustered randomised control trial

Abstract: Background Staff with varying backgrounds and educational qualifications can be effectively trained to implement procedures in line with evidence‐based practice. Behavioural skills training (BST) is a competency‐based training model used to effectively educate a broad selection of professionals, including front line staff, in a range of work‐related skills. However, BST has yet to be evaluated in a large group‐based experiment. Methods This study involved a parallel cluster randomised control trial. Six servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Future research should also consider cost effectiveness in terms of brief skills-based training (e.g. Gormley et al, 2019a) Within the current review a wide variety of measures (both standardized and unstandardized) were used to measure change in participants knowledge, attributions, behavioural explanations and implementation of specific behavioural interventions. Standardized measures had mixed outcomes whereas unstandardized measures all had positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research should also consider cost effectiveness in terms of brief skills-based training (e.g. Gormley et al, 2019a) Within the current review a wide variety of measures (both standardized and unstandardized) were used to measure change in participants knowledge, attributions, behavioural explanations and implementation of specific behavioural interventions. Standardized measures had mixed outcomes whereas unstandardized measures all had positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Berryman et al (1994) and Hardesty et al (2014) reported that participants received orientation training related to behaviour management/behavioural principles and strategies, upon commencing their job. In addition, Berryman et al (1994) described that participants received 2 days of training yearly and asked participants to rate how familiar they were with content of training, similarly in Gormley et al (2019a) participants were asked if they had received training on the specific content taught. In contract, other studies required that participants not to have participated in a comparable training regarding the management of CB for at least 2 years (van Oorsouw et al, 2010) and to not have attended a CB training within the last 6 months (Rose et al, 2014).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 In addition, there is a disconnection between evidencebased practice and the competencies of DSPs. 41 However, it is important to underline that working with PID is very challenging for all DSPs due to the complex nature of ID, 43 44 resulting in DSPs being exhausted and not being able to meet the demands related to their job, and even resulting in burnout. 45 The overall objective of this study is to develop a more qualitative support for PID, enabling them to participate more in MA and by extension in society.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…33 More specifically, the higher the quality of the DSP, the more personal outcomes for PID. 41 Sadly, PID remain underengaged in MA and research on the topic is scarce. More research is needed in order to establish and understand factors that enable or hinder MA.…”
Section: Introductionmentioning
confidence: 99%